Children's Citrus Activity: Citrus Counting - Jamie D Burrow; Ariel Singerman (EDIS, 2019)
Florida is well known for its citrus industry, valued at over eight billion dollars, and is one of the top citrus-producing states in the United States. This new one-page children’s activity sheet about Florida citrus includes an activity for students learning to count and match. Written by Jamie D. Burrow and Ariel Singerman and published by the UF/IFAS Extension 4-H Youth Development Program. https://edis.ifas.ufl.edu/4h402